Performa Lingkungan, Ukuran Perusahaan, dan Performa Perusahaan - Widodo, Agus (Jurusan Akuntansi Politeknik Negeri Pontianak, 2024)
This research aims to find the relationship between environmental performance and company performance in public companies included in the Basic Industry and Chemical subsector categories in 2016-2020. The sample was selected using a purposive sampling technique and obtained 13 companies using the multiple regression analysis method. The research results show that environmental performance variables (Proper) and firm size are proven to influence company performance (Stock prices) in companies that have implemented or are following the Proper program from Kementrian Lingkungan Hidup dan Kehutanan.